Edwardsiella tarda Causing Fishbone Injury Cellulitis Leading to Sepsis in a Case of Hematological Malignancy—A Rare Report and Review of Literature - Sarathi, Sushree; Brahma, Anupam; Das, Prabodha Kumar; Mahapatra, Ashoka; Behera, Bijayini (Journal of Laboratory Physicians, 2023)
Edwardsiella tarda (E. tarda), a gram-negative bacillus, a member of order Enterobacterales, is typically a fish pathogen frequently isolated from fresh and brackish water environments. It is very rarely implicated in human infections such as gastroenteritis (most common), cellulitis, gas gangrene, hepatobiliary infections, peritonitis, empyema, and meningitis. Bacteremia/sepsis caused by E. tarda can be fatal in humans, although very rare (<5%). To date, very few cases of E. tarda sepsis have been reported worldwide including India. We report a rare case of cellulitis caused by E. tarda following fishbone injury in a patient with underlying hematological malignancy leading to sepsis.
Keywords: Edwardsiella tarda; cellulitis; fishbone injury; hematological malignancy; sepsis